2017
DOI: 10.1021/acs.jpca.7b05105
|View full text |Cite
|
Sign up to set email alerts
|

Facile Formation of Acetic Sulfuric Anhydride: Microwave Spectrum, Internal Rotation, and Theoretical Calculations

Abstract: Acetic sulfuric anhydride, CHCOOSOOH, was produced by the reaction of SO and CHCOOH in a supersonic jet. Four isotopologues were observed by microwave spectroscopy. Spectra of both A and E internal rotor states were observed and analyzed, yielding a value of 241.093(30) cm for the methyl group internal rotation barrier of the parent species. Similar values were obtained for the other isotopologues studied. M06-2X/6-311++G(3df,3pd) calculations indicate that the formation of the anhydride proceeds via a π + π +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(52 citation statements)
references
References 37 publications
6
46
0
Order By: Relevance
“…1(c), which is consistent with the mechanism proposed in recent studies. 30,31 3.2 Gas phase cycloaddition reaction of SO 3 to DTAA According to the predicted reaction complex of SO 3 and DTAA, reaction mechanism as well as the energy prole were further calculated. There are two different carboxyl groups (-COOH) in DTAA molecule shown in Fig.…”
Section: Prediction Of the Cycloaddition Reaction Sites Between Dtaa ...mentioning
confidence: 99%
See 1 more Smart Citation
“…1(c), which is consistent with the mechanism proposed in recent studies. 30,31 3.2 Gas phase cycloaddition reaction of SO 3 to DTAA According to the predicted reaction complex of SO 3 and DTAA, reaction mechanism as well as the energy prole were further calculated. There are two different carboxyl groups (-COOH) in DTAA molecule shown in Fig.…”
Section: Prediction Of the Cycloaddition Reaction Sites Between Dtaa ...mentioning
confidence: 99%
“…28 Furthermore, recent studies have shown that except the dominant reaction of sulfur trioxide (SO 3 ) with water vapor in the troposphere, 29 cycloaddition reaction of SO 3 to carboxylic acids is a possible formation mechanism of carboxylic sulfuric anhydrides which would have lower vapor pressure than the corresponding carboxylic acids and have more inter-molecular interaction sites. [30][31][32] It is hence speculated that the contribution of DTAA to new particle formation may be improved by the reaction with SO 3 to generate diaterpenylic acetate sulfuric anhydride (DTASA, C 10 H 16 O 9 S).…”
Section: Introductionmentioning
confidence: 99%
“…This reaction also involves a low free‐energy barrier of activation (2.5 kcal mol −1 for FA, Figure S1). It provides a mechanism for incorporating organic matter into aerosol particles …”
Section: Figurementioning
confidence: 99%
“…Although both of the above mechanisms for the reaction between organic acids and SO 3 can explain the enhanced particle formation to some extent, they are still limited to the gas phase. In the atmosphere, liquid phases are abundant in the form of clouds, aerosols, or sea‐salt particles.…”
Section: Figurementioning
confidence: 99%
“…Due to higher resolution and more accurately determined molecular parameters in comparison to, for example, fluorescence or electronic spectroscopy, many barriers to internal rotation have been determined by this method. [1][2][3] The barrier height varies in a wide range, but could be classified in three main classes. The first class comprises molecules with high barriers (>600 cm −1 ) with ethyl chloride as a typical example (1200 cm −1 ).…”
Section: Introductionmentioning
confidence: 99%